High coverage of hepatitis B vaccination and low prevalence of chronic hepatitis B in migrant children dictate a new catch-up vaccination strategy. Issue 30 (16th July 2018) - Fougère, Yves; El Houss, Samir; Suris, Joan-Carles; Rouvenaz-Defago, Sylvie; Miletto, Damien; Von der Weid, Lucie; Willen, Fanny; Williams-Smith, Joanne Anesta; Gehri, Mario; Crisinel, Pierre Alex
Abstract: Background: Worldwide coverage of hepatitis B (HB) vaccination is increasing. This should be considered when determining the best strategy for catch-up HB vaccination in migrant children, who rarely have written proof of past immunizations. This study aimed to estimate HB vaccine protection, chronic HB prevalence and to identify determinants of vaccine protection. Methods: Newly arrived migrant children at Lausanne University Hospital from October 2014 to July 2017 were prospectively enrolled. Children and adolescents aged 1–18 years were approached for inclusion if they had no proof of past vaccinations and accepted a single dose of injected HB vaccine. HB surface antibody (anti-HBs) serology was performed after 4–6 weeks. Anti-HBs ≥100 IU/L were considered consistent with a booster-type antibody response. Patients with anti-HBs <100 IU/L received additional dose(s) of HB vaccine, after exclusion of chronic HB in children with anti-HBs <10 IU/L. Potential determinants of vaccine response were compared between children with and without booster-type response. Results: Two hundred children were available for analysis. Median age was 8.9 years (IQR 4.8–12.9), and 97 (49%) were female. The majority (n = 124, 62%) came from the region classified by the WHO as eastern Mediterranean. One hundred and sixty-one children (81%) had a booster-type antibody response. Only 1 patient (<1%) had chronic HB. In the multivariate analysis, younger age (OR per decreasing-year, 1.28; 95%CI, 1.05–1.57; p = 0.017) and migration from an urban area (OR 1.16; 95%CI, 1.01–1.33; p = 0.043) were the only significant determinants of booster-type response. Conclusion: Post-vaccine serology may be used to identify a high proportion of individuals in our pediatric migrant population with previous immunization for HB. Our study also showed extremely low prevalence of chronic HB. No variable could definitively determine the results of serology. Post-vaccine serology represents the most effective strategy in this context of high vaccine coverage.